Influence of Policy Implementation, Leadership and Professionalism toward Performance of Man Power Dines of Bekasi Municipality West Jawa Province - Wahyu Tri Putranto; Wirman Syafri; Prio Teguh; Irwan Tahir (Budapest International Research and Critics University, 2022)
The phenomenon that is used as the object of research is the performance of Manpower Dines of Bekasi City. The purpose of the study was to discuss the influences of Policy Implementation, Leadership and Professionalism toward the Performance of of Manpower Dines of Bekasi City. The research uses quantitative research. The research sample was 242 respondents taken from a population of 667 people using the Krejcie Table. Data collection techniques using literature study, questionnaire and observation techniques. Data analysis using SEM analysis. The results of the study are as follows: The magnitude of the influence of Policy Implementation toward the Performance of Manpower Dines of Bekasi City reached 0.30, which was weak but significant. The magnitude of the influence of leadership toward the performance of Manpower Dines of Bekasi City reached 0.52, which is quite strong and significant. The magnitude of the influence of professionalism toward the performance of Manpower Dines of Bekasi City reached 0.33, which was weak but significant. The new concept that can be compiled from the discussion of the results of research on the influence of Policy Implementation toward the Performance of Manpower Dines of Bekasi City is Financial Governance of Regional Work Units. The new concept that can be compiled from the discussion of the results of research on the influence of Leadership toward the Performance of Manpower Dines of Bekasi City is Organizational Behavior Steering Leader. The new concept that can be compiled from the discussion of the results of research toward the influence of Professionalism toward the Performance of Manpower Dines of Bekasi City is Professional Appearance.